ChemInform Abstract: Niobic Acid Nanosheets Synthesized by a Simple Hydrothermal Method as Efficient Broensted Acid Catalysts. Issue 43 (7th October 2013) - Fan, Wenqing; Zhang, Qinghong; Deng, Weiping; Wang, Ye
Abstract Nb2O5·xH2O nanosheets are hydrothermally synthesized from mixtures of NbCl5 dissolved in EtOH and aqueous NH3 solutions (autoclave, 513 K, 24 h).